On the Boundedness of a Generalized Fractional Integral on Generalized Morrey Spaces - Eridani (Limits: Journal of Mathematics and Its Applications, 2006)
In this paper we extend Nakai's result on the boundedness of a generalized fractional integral operator from a generalized Morrey space to another generalized Morrey or Campanato space.